Pengelolaan Lanskap Rumah Sakit Umum Daerah Patut Patuh Patju Kecamatan Gerung Kabupaten Lombok Barat Provinsi Nusa Tenggara Barat - PERMANA, FIRMAN; SARWADANA, SANG MADE; MAYADEWI, NI NYOMAN ARI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.1, Januari 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT The Landscape Management of Patut Patuh Patju Hospital Sub district of Gerung, West Lombok District, the Province of Nusa Tenggara The Garden of RSUD Patut Patuh Patju West Lombok Regency is under the head of Employment and General Subdivision. The working system on landscape management and cultivation garden now is need to be increased to revise an old concept that regarded as less shade, smooth, view and building unification its far from comfortable impression, and to look for the answer as well comparison in the cultivation of environment hygiene application management and gardens system that has been applied since 2005 up to now. Research purposes are to know : 1) pattern of landscape management used and how far the system applied by landscape management side, 2) the effectiveness landscape management activity applied, and 3) factors are barriers in the accuracy to determine functions and main jobs of landscape management. Results of the research show that landscape are quite large in several parts, whereas generally landscape condition is precisely good from plantation aspect and physical garden available, so users feel comfortable, peaceful and shaded. Precisely good condition of landscape but not supported by its optimal of landscape management in cultivation plantation, cutting and watering. These are showed by (75,6%) respondents as well fertilization is rarely done 53,7%. Then (36%) of respondents said do not know and the function of carrying on process has not proper yet on the object landscape handled (34,1%). The manager has done the duty correctly. That is proved by 43,6% of respondents, but they have not done the management factors appropriately yet Keywords : hospital landscape management, plantation, and comfortable